2005
DOI: 10.11646/zootaxa.933.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A new Gymnotus (Teleostei: Gymnotiformes: Gymnotidae) from the Pantanal Matogrossense of Brazil and adjacent drainages: continued documentation of a cryptic fauna

Abstract: Here we describe a new species of Gymnotus, G. pantanal n. sp., from the Pantanal Matogrossense of Brazil, using morphological, cytogenetic, and molecular data. Specimens ascribed to the new species are also known from areas downstream in Paraguay, and from the adjacent Guaporé basin of Bolivia. The new species most closely resembles G. anguillaris in possessing an elongate body, slender profile, long body cavity, and shorter head than other congeners. The new species also resembles G. anguillaris in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 9 publications
1
40
0
1
Order By: Relevance
“…The only gymnotid genus recorded in the upper rio Paraná basin is Gymnotus, monophyletic and the most diverse and widespread of South American electric fishes (Fernandes et al, 2005), with a single species previously found in this basin: G. carapo. Electrobiological, cytogenetic and molecular studies have shown that Gymnotus currently encompasses numerous different species throughout the Neotropical region, some of which are still undescribed (Campos-da-Paz, 2003).…”
Section: Gymnotidaementioning
confidence: 93%
“…The only gymnotid genus recorded in the upper rio Paraná basin is Gymnotus, monophyletic and the most diverse and widespread of South American electric fishes (Fernandes et al, 2005), with a single species previously found in this basin: G. carapo. Electrobiological, cytogenetic and molecular studies have shown that Gymnotus currently encompasses numerous different species throughout the Neotropical region, some of which are still undescribed (Campos-da-Paz, 2003).…”
Section: Gymnotidaementioning
confidence: 93%
“…Materials examined are listed in Campos-da-Paz & Costa (1996), Albert (2001), Albert & Crampton (2001, Campos-da-Paz (2002), Crampton et al (2003, Maldonado-Ocampo & Albert (2003), Fernandes et al (2005), Cognato et al (2007), and Richer-deForges et al (2009 …”
Section: Methodsmentioning
confidence: 99%
“…Counts and measurements followed Albert (2001) and Fernandes et al (2005). When referring to Gymnotus pantanal sensu stricto or typical color pattern we followed Fernandes et al (2005), who found a color pattern of obliquely-oriented thin pale pigment bands.…”
Section: Morphological Analysismentioning
confidence: 98%
“…Gymnotus pantanal was described by Fernandes et al (2005) in the Paraná-Paraguay system, in Brazil and Paraguay, and in the River Chapare-Mamoré, in Bolivia. Fernandes et al (2005) used morphological, cytogenetic, and molecular data to describe that species; in their diagnosis color pattern was the main morphological trait: 'Gymnotus pantanal differs from other members of the G. pantherinus Steindachner speciesgroup (except G. anguillaris Hoedeman) in possessing a color pattern composed of thin obliquely-oriented pale pigment bands (about one third the width of the dark bands) with wavy margins restricted to the ventral portion of the body (rarely extending above the lateral line) on the anterior half of the body'. Later, Graça & Pavanelli (2007) and Margarido et al (2007) reported this species for the upper Paraná River basin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation